Water security in North Carolina’s most economically insecure county: a case study - Hana C Long; Beverly Collins-Hall; Kaelan Moore; Bethany Cutts; Jacqueline MacDonald Gibson (Environmental Research Letters)
Negative health impacts of water insecurity are often felt most in poor and rural communities and communities of color, who are more likely to be underserved by water infrastructure and disproportionately subject to socioeconomic stressors. Despite mandated efforts to allocate significant federal resources to infrastructure funding in ‘disadvantaged communities,’ communities with the most need risk systematic exclusion from access to resources, decision-making structures, and even benefits of research intended to address inequitable infrastructure services and health outcomes in their own communities. This project aims to describe groundwork and preliminary findings from community-engaged environmental research conducted within an ongoing community-based participatory research partnership in Robeson County, NC, a majority–minority county with the lowest median household income of NC’s 100 counties. Semi-structured interviews conducted with community members were analyzed to identify concerns about drinking water security (including safety, affordability, and reliability), perceptions of water quality, averting behaviors taken due to water insecurity, and ideas for improving water security. Findings suggest that there is a high level of mistrust in community water supplies, with perceptions of poor water quality driving a reliance on bottled water. Those relying on private wells expressed greater trust in their water and lower reliance on bottled water. Concerns about affordability were less prominent than those about water quality. Insufficient water reliability (low flow) was mentioned by many respondents, including those with community water service and those relying on private wells. Most supported increasing taxes to improve water security and also recommended increasing communications between water service providers and the public to improve trust. Overall, this work suggests the need for a comprehensive assessment of the quality and reliability of community water services in Robeson County, interventions to address problems identified, and much more engagement with the community about identifying and allocating funding to solve water security problems.